Exchange market pressure : evidence from asia nation - Yong, Jenny Lijoo (Universiti Malaysia Sarawak (UNIMAS), 2011)
The main purpose of this study is to examine the relationship between EMP, consumer price index, real gross domestic product, narrow money, domestic interest rate and foreign interest rate in 7 selected Asian countries; Hong Kong, Indonesia, Thailand, Malaysia, South Korea, Singapore and Japan started from the period 1993 until 2010 using quarterly data. Two model approaches are applied in this study; model dependent and model independent. Unit root, Johansen and Juselius cointegration test, vector error correction model (VECM) and variance decompositions (VDCs) are used to examine the model. In general, consumer price index, real gross domestic product, narrow money, domestic interest rate and foreign interest rate are found to be significant and have negative impact on EMP. Besides that, long-run relationship also existed between the variables and EMP. Therefore, monetary policies are needed in order to control the volatility of exchange rate